The Correlation between the Teacher's Oral Feedback and the Students' Writing Motivation - Irawan, Rifki; Dininorani Seran, Edita (FOSTER: Journal of English Language Teaching, 2021)
This study aims to determine the correlation between the teacher’s oral feedback and the students’ writing motivation. This study is quantitative research with a correlation method. The researcher conducted this study at SMPN 2 Kasihan. The population of this study included all of the 8th graders. The sample of this study consists of 93 students. To gain the data, the researcher distributed the questionnaires to the students. The data analysis technique used in this research used Rank Spearman Correlation, with SPSS version 23 for the windows program. The result of the research showed that there is a correlation between the teacher’s oral feedback and the students’ writing motivation. It is evidenced by the Rank Spearman correlation test results with the significance value of 0.000, where it is <0.05.